The Potential of Contingent Valuation for Planning Practice. The Example of Dortmund Westpark - Wilker, Jost; Gruehn, Dietwald (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
This paper highlights the practical opportunities that contingent valuation can deliver to improve park management. Although green infrastructure, such as urban parks, provides huge benefits to society, investments require a strong economic justification and have to be based on societal needs and preferences. Accordingly, this paper investigates, by means of a survey of willingness to pay and willingness to work, how users value possible improvements to the management of Dortmund Westpark, and which determinants influence their decisions. In line with the scientific discussion of integrating economic valuation in decision making, we introduce a simple approach to applying valuation results to planning. Total willingness to pay and willingness to work are set in proportion to the real-time costs of suggested proposals. To make the findings useful for park management, these proposals consider the weighting of users’ preferences. Total hypothetical working hours are also integrated into the approach by proposing where they could be used most effectively. Our study reveals the high social values people attach to park improvements and demonstrates the potential benefits of contingent valuation study results for decision making.